2020
DOI: 10.1016/j.heliyon.2020.e03916
|View full text |Cite
|
Sign up to set email alerts
|

Patients perceptions of virtual reality therapy in the management of chronic cancer pain

Abstract: The management of chronic cancer pain remains challenging and complex, with the process often involving a variety of pharmacological and non-pharmacological approaches. Recent studies have shown virtual reality (VR) therapy to be successful in the management of acute pain. However, it remains unclear whether VR-based applications are effective as an adjunctive therapy for cancer patients with chronic pain. Moreover, there exists a gap in the current research landscape that address patient's perceptions of virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 48 publications
2
77
0
12
Order By: Relevance
“…However, the type of cancer in each study differs considerably, as shown in Table II. Approximately, 23% of the papers were focused on breast cancer treatments [22], [23], [26], [27], [28], [31], [35], [37], [39], [41] followed by blood cancer (e.g., leukaemia, lymphoblastic, etc.) (12%) [21], [25], [33], [36], [38], bone cancer (12%) [25], [29], [33], [38], [40], and brain cancer (12%) [25], [32], [33], [38], [40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the type of cancer in each study differs considerably, as shown in Table II. Approximately, 23% of the papers were focused on breast cancer treatments [22], [23], [26], [27], [28], [31], [35], [37], [39], [41] followed by blood cancer (e.g., leukaemia, lymphoblastic, etc.) (12%) [21], [25], [33], [36], [38], bone cancer (12%) [25], [29], [33], [38], [40], and brain cancer (12%) [25], [32], [33], [38], [40].…”
Section: Resultsmentioning
confidence: 99%
“…(12%) [21], [25], [33], [36], [38], bone cancer (12%) [25], [29], [33], [38], [40], and brain cancer (12%) [25], [32], [33], [38], [40]. Various studies examined lymphoma cancer (9%) [25], [33], [38], [39] and lung cancer (7%) [20], [30], [35] while some studies focused on sarcoma (5%) [32], [40], and germ cell tumors (5%) [33], [38]. A few studies assessed the VR impact on cancer related to ovaries [40], melanoma [38], abdominal [39], throat [39], and metastatic [24] types of cancer (2% each).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations